Golden Law in Brazil, parties in Lagos (Nigeria): identity and representation - da Silva, Angela Fileno (ODEERE, 2016)
This paper presents and discusses the life of Bento de Jesus, Catholic lay brother of the Franciscan Order who acted as preacher in Cape Verde during the first half of the 17th century and was condemned to death by the Portuguese Inquisition after a mystical experience which was considered heretical. The contents of his mystical vision will be analysed , as well as the way Bento de Jesus experienced and understood the Catholic dogma and trasmitted it to other Africans in Cape Verde. We intend to show that his preachings, by focusing penitencialist practices and conceptions, reinforced the main aspects of a discourse disseminated in the Portuguese Atlantic world by the Jesuits, according to which African slavery could be considered legitimate because it was represented as a necessary means to purge the alleged sins of African populations. Taking into account the fact that Bento de Jesus was himself and African and a direct descendant of slaves, the paper aims to discuss how the Catholic ideology of slavery was appropriated by Africans in ambivalent (and sometimes deviant) ways, reinforcing slavery discourse s and, at the same time, exposing some of their contradictions. Keywords: ideology of slavery, African Catholicism, Inquisition, Catholic Church, Cape Verde